An omnidirectional wrappable compact patch antenna for wireless endoscope applications (2012)
An inductively loaded compact patch antenna for a radiation frequency of 433 MHz is designed taking into consideration a human-body model and fabricated on a flexible liquid crystalline polymer (LCP) substrate, which is subsequently wrapped into a cylindrical shape to achieve a monopole-like omnidirectional radiation pattern for wireless endoscope applications. The wrapped patch antenna has a stretched length of 31 mm (0.07λ), and its cylindrical form has a diameter of 10 mm and a width of 18.5 mm, whose dimensions are designed to be comparable to those of a commercially available capsule endoscope. Compared to a traditional patch antenna with the same radiation frequency, an 86% length reduction is achieved. Omnidirectionality is desired to increase the space coverage in communication between the randomly moving capsule inside and the receiver outside the body. The enclosed cylindrical cavity, surrounded by the ground plane of the patch, provides an electromagnetic interference (EMI) protected room that is useful for the placement of other electronic components. Multiple inductive notches on a patch designed for antenna size reduction are described by an equivalent circuit model. Human-body phantom solution is used for antenna characterization. The antenna, located at the outermost layer, serves not only as a good radiating unit, but also as the EMI protecting, mechanically supporting, packaging layer of the endoscope system. © 2002-2011 IEEE.